Abnormal social behavior and altered gene expression in mice lacking NDRG2. (19th January 2021) - Takarada-Iemata, Mika; Yoshihara, Toru; Okitani, Nahoko; Iwata, Keiko; Hattori, Tsuyoshi; Ishii, Hiroshi; Roboon, Jureepon; Nguyen, Dinh Thi; Fan, Qiyan; Tamatani, Takashi; Nishiuchi, Takumi; Asano, Masahide; et al.
Highlights: NDRG2 expression increased during postnatal brain development. NDRG2 deficiency altered gene expression in the brain, including Bmp4 and Per2 . NDRG2 knockout mice showed abnormal social behavior. Abstract: N-myc downstream-regulated gene 2 (NDRG2), a member of the NDRG family, has multiple functions in cell proliferation, differentiation, and stress responses, and is predominantly expressed by astrocytes in the central nervous system. Previous studies including ours demonstrated that NDRG2 is involved in various central nervous system pathologies. However, the significance of NDRG2 in neurodevelopment is not fully understood. Here, we investigated the expression profile of NDRG2 during postnatal brain development, the role of NDRG2 in social behavior, and transcriptome changes in the brain of NDRG2-deficient mice. NDRG2 expression in the brain increased over time from postnatal day 1 to adulthood. Deletion of NDRG2 resulted in abnormal social behavior, as indicated by reduced exploratory activity toward a novel mouse in a three-chamber social interaction test. Microarray analysis identified genes differentially expressed in the NDRG2-deficient brain, and upregulated gene expression of Bmp4 and Per2 was confirmed by quantitative PCR analysis. Expression of both these genes and the encoded proteins increased over time during postnatal brain development, similar to NDRG2. Gene expression of Bmp4 and Per2 was upregulated in cultured astrocytes isolated from NDRG2-deficient mice. These results suggest that NDRG2 contributes to brain development required for proper social behavior by modulating gene expression in astrocytes.